O Turismo Rural Pedagogico como Estratégia para a Valorização do Patrimonio Cultural e Natural nas Areas Rurais - Elesbão, Ivo [UNESP]; Klein, Angela Luciane; Souza, Marcelino de (Fronteiras: Journal of Social, Technological and Environmental Science, 2022)
The transformations that have taken place in rural areas have contributed to the configuration of a new rural reality. It is marked by the dynamism and diversity of services and new jobs. In this scenario, new socioeconomic activities are beginning to emerge, favoring the generation of jobs and income. In the same time it is also improving the enhancement of natural and cultural heritage. This is the case of Pedagogical Rural Tourism, characterized by a set of educational practices carried out within the scope of rural property. It uses agricultural activities, agricultural production and the present natural and cultural assets as a didactic resource. In these terms, this study aims to present the contributions of Pedagogical Rural Tourism as a strategy that favors the enhancement of cultural and natural heritage in rural areas. Methodologically, three scientific studies developed by a group of researchers were used as the basis of analysis in this thesis. Those researches are from Federal University of Rio Grande do Sul and the studies have carried out in the south and southeast of Brazil between the years 2012 and 2015. The analysis included the following four different experiences: the Roadmap of Rural Routes of Porto Alegre (RS); the Viva Ciranda Project (Joinville - SC); the Rural Tourism and School Project - Fazer Eco (Brasília, DF) and the Pedagogical Rural Tourism Route of the State of São Paulo (São Paulo). The results highlight that such activity not only contributes to the visibility and valorization of agriculture and rural spaces. It also assign them new functions (educational, environmental, social, patrimony), and even more stimulates the interaction between countryside and city, the preservation of the environment and the conservation of rural culture. From this it can be concluded, that Pedagogical Rural Tourism emerges as an effective alternative, whose potentials can range different levels, from the economic and social, until the environmental and cultural.
Keywords: cultural patrimony; environmental education; new rural; pedagogical rural tourism